Al-Aṣwāt wa Āthāruhā fī Maʿānī al-Kalimāt al-ʿArabiyyah - Arid Adi Setiawan (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2014)
Speech sounds play a fundamental role in language in general and in the Arabic language in particular. As Ibn Jinnī explains in his book Al-Khaṣāʾiṣ, language consists of sounds through which people express their intentions and ideas. Since sounds constitute the foundation of language, they influence all internal linguistic elements, including words, sentences, and meaning. Consequently, there is a close relationship between phonetics and semantics. Arabic speech sounds are distinguished by the systematic distribution of their articulation points, creating balance and harmony among the sounds. This relationship is reflected in the correspondence between the sequence of articulatory movements and the sequence of events expressed by words, as illustrated by pairs such as kharaja (to go out) and dakhala (to enter). Furthermore, each Arabic consonant possesses distinctive phonetic characteristics that differentiate it from others. Words sharing two of their original root consonants often share certain semantic features, whereas a change in one root consonant generally results in a corresponding change in meaning. This semantic distinction arises from the different phonetic properties of the consonants, as demonstrated by the contrast between al-waṣīlah and al-wasīlah. The article highlights the significant relationship between Arabic phonology and lexical meaning.